2008
DOI: 10.1371/journal.pone.0003302
|View full text |Cite
|
Sign up to set email alerts
|

P38 MAP Kinase Signaling Is Required for the Conversion of CD4+CD25− T Cells into iTreg

Abstract: CD4+CD25+ regulatory T cells (Treg) are important mediators of immune tolerance. A subset of Treg can be generated in the periphery by TGF-beta dependent conversion of conventional CD4+CD25− T cells into induced Treg (iTreg). In chronic viral infection or malignancy, such induced iTreg, which limit the depletion of aberrant or infected cells, may be of pathogenic relevance. To identify potential targets for therapeutic intervention, we investigated the TGF-beta signaling in Treg. In contrast to conventional CD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
39
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(44 citation statements)
references
References 31 publications
4
39
0
Order By: Relevance
“…Transplanted mice were injected with pertussis toxin (PT) on the day of T cell transfer and 48 hours later and monitored for the development of EAE. We found that mice that received Th17 cells differentiated in the presence of control TGF-β signaling through SMAD-dependent and SMAD-independent pathways plays a role in Treg differentiation and function (56)(57)(58)(59)(60)(61). Although TGF-β signaling through the SMAD-2/3 pathway has been demonstrated to partially regulate iTreg differentiation, it has also been shown that a combination of SMAD-2 and SMAD-3 deficiency does not alter FOXP3 expression or the suppressive activity of iTregs in vivo (58).…”
Section: Silencing Mir-21 Ameliorates the Clinical Severity Of Eaementioning
confidence: 95%
See 1 more Smart Citation
“…Transplanted mice were injected with pertussis toxin (PT) on the day of T cell transfer and 48 hours later and monitored for the development of EAE. We found that mice that received Th17 cells differentiated in the presence of control TGF-β signaling through SMAD-dependent and SMAD-independent pathways plays a role in Treg differentiation and function (56)(57)(58)(59)(60)(61). Although TGF-β signaling through the SMAD-2/3 pathway has been demonstrated to partially regulate iTreg differentiation, it has also been shown that a combination of SMAD-2 and SMAD-3 deficiency does not alter FOXP3 expression or the suppressive activity of iTregs in vivo (58).…”
Section: Silencing Mir-21 Ameliorates the Clinical Severity Of Eaementioning
confidence: 95%
“…In fact, the development, homeostasis, and function of Tregs remained intact in SMAD-2 and SMAD-3 doubledeficient mice, suggesting a role for a SMAD-independent pathway in Treg differentiation and function (60). Among the SMAD-independent TGF-β signaling pathways, p38 MAPK signaling has been shown to be required for the conversion of naive CD4 + T cells into iTregs (61). Furthermore, IL-2 has been shown to stabilize TGF-β-induced FOXP3 expression and compensate for the loss of defective SMAD-dependent TGF-β signaling in iTreg differentiation (21).…”
Section: Silencing Mir-21 Ameliorates the Clinical Severity Of Eaementioning
confidence: 99%
“…We now suspect that the dominant p38 activation in response to other MAPK (ERK and JNK) in in vivo Ag-induced iTreg is related to both the suppressor function via IL-10 production and the anergic state via cell cycle arrest and p27 expression and not via IL-10 [14]. Recent studies have indicated that p38 activation is required for TGF-b-induced in vitro conversion to iTreg [23,24] and is involved in IL-10 production via innate TLR2 signaling of HSP60 in iTreg [25] or in the induction to iTreg through tDC treated with CpG [26]. We suspect that p38-dependent IL-10 production is mediated by TAB1.…”
Section: Il-10-producing Cd25mentioning
confidence: 99%
“…Recently it has been reported that Smad3 (42) and p38 MAPK activation (43) play an important role for the conversion of CD4 ϩ CD25 Ϫ T cells into iTreg.…”
Section: Activin a Induces The Activation Of Smad2 And P38 Mapkmentioning
confidence: 99%